Comparison of the cytotoxic effects of different fractions of Artemisia ciniformis and Artemisia biennis on B16/F10, PC3 and MCF7 Cells - Elham Ramazani; Zahra Tayarani-Najaran; Yalda Shokoohinia; Mahdi Mojarrab (Wolters Kluwer Medknow Publications, 2020)
Background and purpose: Artemisia is one of the well-known herbal medicinal plants for antimicrobial, insecticidal, antioxidant, and antimalarial activities. The antiproliferative effects of dichloromethane extracts of Artemisia biennis (A. biennis) and A. ciniformis and the petroleum ether extract of A. ciniformis have been demonstrated previously on human cancerous cell lines. In the current study, further fractionation was carried out on the aforementioned extracts and their cytotoxic effects were evaluated on three human cancer cell lines; B16/F10, PC3, and MCF7. F1 to F16, F1' to F11', and F1" to F10" were resulted from the fractionation of dichloromethane extracts of A. biennis, A. ciniformis, and petroleum ether extract of A. ciniformis, respectively. Experimental approach: The cytotoxic effects of 16 (F1-F16), 11 (F1'-F11') and 10 (F1"-F10") fractions, on B16/F10, PC3, and MCF7 cell lines were assessed using resazurin to measure viability and propidium iodide staining (sub G1) and flow cytometry to detect apoptosis. Findings / Results: The results showed that, some fractions at 100 μg/mL decreased cell viability. F2" in B16/F10 cells, F2, F4-F6, F10', F11', and F2" in PC3 cells, and F10', F11', and F2" in MCF7 significantly decreased cell viability in a concentration-dependent manner (12.5-50 μg/mL). Among different fractions, F2" demonstrated the most potent cytotoxic effects on cancer cell lines (P < 0.001). All of the mentioned fractions (except F11' on PC3 cells) increased the number of apoptotic cells and showed the cytotoxic effects on cancer cells compared with the control group. Conclusion and implications: A. biennis and A. ciniformis are suggested as the potential sources of cytotoxic phytochemicals. The probable presence of terpenoids, steroids, and alkaloids in the selected fractions is proposed based on the preliminary phytochemical study.